Techniques of protection and revascularization of the bronchial anastomosis - Venuta, Federico; Diso, Daniele; Anile, Marco; Rendina, Erino A. (Journal of Thoracic Disease, 2016)
Airway anastomosis has been traditionally considered at risk for the onset of complications, particularly dehiscence with consequent infection and erosion in the adjacent vessels. Although the modifications and improvements of the surgical technique has contributed to reduce the incidence of complications, the protection and revascularization of the anastomotic site is still considered mandatory at many centers Many techniques have been proposed for encircling the bronchial anastomosis.